"Recovery is fearful to me...": Conceptualizations, concerns and hopes about personal recovery in adults who are chronically homeless. Issue 3 (4th May 2023) - Karadzhov, Dimitar
ABSTRACT: This qualitative investigation explored how 18 chronically homeless adults with serious mental illness residing in emergency and temporary supportive housing facilities in Glasgow, Scotland, and New York City conceptualized personal recovery. Thirty-six interviews were conducted and analyzed using interpretative phenomenological analysis. The analysis produced four superordinate themes revealing how participants engaged with, envisioned, or disidentified with, the recovery idea, in the context of chronic life adversity, co-occurring conditions, a precarious present and an uncertain future. Health and social care providers should be responsive to clients' diverse ideas about recovery and facilitate their exploration of authentic pathways to a "good life."